Ditransitive Constructions in Zaza Language - İlyas Arslan (Akademik İncelemeler Dergisi)
Languages group verbs in different ways. Because of the ergative feature of Zazaki, it plays a big role whether the verbs are transitive or intransitive. Zaza Language introduces some pronouns to distinguish double-transitive verbs from transitive and intransitive verbs. In some linguistic works, the terms transitive and ergative are used synonymously. This article aims to scrutinize ditransitive constructions in the Zaza language, which has some interesting syntactic elements in these structures. They are mostly pronouns in combination with directions. Several pronouns replace indirect object. On the one hand, the goal of this study is to find out the functions of these pronouns. The semantic content of these pronouns decides which pronouns may appear in a specific position. They can appear with or without directions. Only the pronouns such as cı can alone replace a NP, the other ones need a direction for this replacing. On the other hand, this study discusses the morphosyntactic and semantic realizations in ditransitive constructions. While these pronouns do not syntactically follow the same word order, they can semantically be classified into two groups.